2022
DOI: 10.3390/jpm12091406
|View full text |Cite
|
Sign up to set email alerts
|

A Differential Profile of Biomarkers between Patients with Atrial Fibrillation and Healthy Controls

Abstract: Atrial fibrillation (AF) is explained by anatomical and electrophysiological changes in the atria determined by high pressure, dilatation, infiltration and inflammation in the myocardium. There are some biomarkers implicated in these processes, namely, NT-proBNP, high sensitivity troponin (Hs-Tn), urate, galectin-3, ST2, C reactive protein and fibrinogen. The aim of this study was to assess differences in these biomarkers between patients with AF and healthy controls. We designed a cross-sectional study consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…After reading the full text, 14 studies were further excluded because 3 were reviews, 5 were irrelevant findings, and the other 6 were inadequate data. Finally, 24 studies ( 12 14 , 17 37 ) were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the full text, 14 studies were further excluded because 3 were reviews, 5 were irrelevant findings, and the other 6 were inadequate data. Finally, 24 studies ( 12 14 , 17 37 ) were included.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 displayed the baseline characteristics of 24 included studies from 2015 to 2022, comprising 14 prospective studies ( 14 , 17 23 , 26 , 29 31 , 33 , 37 ), 4 retrospective studies ( 24 , 25 , 27 , 32 ), 4 cross-sectional studies ( 12 , 13 , 34 , 35 ), and 2 case-control studies ( 28 , 36 ). Eleven studies were conducted in Asia (China, Thailand, Singapore), 10 studies in Europe (Germany, Poland, Finland, France, Norway, Spain, Sweden, Turkey), and 3 study in America (The united states).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that abnormal biomarker concentrations reflecting cardiac and renal dysfunction as well as inflammation and oxidative stress identify patients at higher risk of developing AF. Merino-Merino et al [ 43 ], in a recent study comparing AF patients with healthy study participants, showed a relationship between NT-proBNP, ST2, high-sensitivity cardiac troponin T, and the presence of AF, with NT-proBNP showing the highest yield in differentiating patients with AF from healthy participants.…”
Section: Discussionmentioning
confidence: 99%
“… 16 However, a comprehensive assessment of AF by combining several biomarkers has not been fully established. 17 Further, the differential metabolites (DMs) of different types of AF are not well established.…”
mentioning
confidence: 99%